2012
DOI: 10.1016/j.ccr.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNA Polymerase I as a Therapeutic Strategy to Promote Cancer-Specific Activation of p53

Abstract: Increased transcription of ribosomal RNA genes (rDNA) by RNA Polymerase I is a common feature of human cancer, but whether it is required for the malignant phenotype remains unclear. We show that rDNA transcription can be therapeutically targeted with the small molecule CX-5461 to selectively kill B-lymphoma cells in vivo while maintaining a viable wild-type B cell population. The therapeutic effect is a consequence of nucleolar disruption and activation of p53-dependent apoptotic signaling. Human leukemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
606
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 479 publications
(674 citation statements)
references
References 38 publications
48
606
2
3
Order By: Relevance
“…The data suggest that targeting the nucleolar proteome may elicit the required signaling events to cell cycle regulators without affecting rRNA production and ribosome biosynthesis. This may be important as targetting Pol I activity is emerging as an attractive anti cancer approach 55,56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that targeting the nucleolar proteome may elicit the required signaling events to cell cycle regulators without affecting rRNA production and ribosome biosynthesis. This may be important as targetting Pol I activity is emerging as an attractive anti cancer approach 55,56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…2, 9-11]. In particular, the robust upregulation of genes encoding all members of the RNA polymerase I (Pol I) complex, which is responsible for transcription of the 47S pre-rRNA encoding genes (rDNA), is a key component of MYC's gene expression signature (9,10,12,13). Importantly, we recently demonstrated that rDNA transcription, a key ratelimiting step for ribosome biogenesis, is specifically targeted by the novel small-molecule inhibitor CX-5461, which is currently in phase I trial (14).…”
Section: Research Briefmentioning
confidence: 99%
“…The RNA Pol I inhibitor CX5461 has shown therapeutic potential in mouse leukemia model. 17 It will be important to investigate the role of RNA Pol I inhibition in solid tumors that have low apoptotic potential and rely on senescence as a treatment response mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the RNA Pol Ispecific inhibitor CX5461 has shown promise as an anti-tumor agent in animal models, in part by activating p53 through the nucleolar stress signaling mechanism that inhibits MDM2 function. 16,17 Nearly 50% of rDNA repeats are present as heterochromatin in growing cells, which is important for maintaining genetic stability. 18 The NoRC (nucleolar remodeling complex) is important for switching rDNA between silent and active state.…”
Section: Introductionmentioning
confidence: 99%